RECONSTRUCTION CREASE FOR FINGERPRINT IMAGES USING MINUTIA DENSITY DISTRIBUTION: AN EMPIRICAL STUDY - Firas S. Abdulameer; Firas S. Abdulameer; Kuba Hasanien Kariem (European Journal of Research Development and Sustainability, 2022)
Fingerprint recognition is one of the secure techniques for automatic personal identification, and it is one of the safe techniques for automatic personal identification. . It is receiving more and more attention and is frequently used in civil applications like access control and financial security. One of the critical elements in image processing applications that refer to human traits for user verification is the fingerprint. In real terms, wrinkles will split ridgelines and create a string of false minutiae, fatally destroying the structure and texture of a fingerprint. Wrinkles will thereby decrease the accuracy of the fingerprint identification algorithm, especially in the leading technique based on minutiaematching. In this article, we investigate two elements of the treatment of wrinkles and ridge reconstruction using fingerprint photos. To start, we calculate the distance between pseudo minutiae pairing. Then, we reconstruct ridges based on midpoint criteria of a line segment with endpoints. The outcomes are presented in the paper.